Digital innovation and human rights: dilemmas in international law enforcement practice - M. A. Mikhailov; T. A. Kokodey (Правоприменение, 2022)
The subject of the study is the legal nature of personal data, as well as a set of legal norms governing relations in the field of their processing and circulation in the Russian Federation and foreign countries. The article uses a comparative method, a system analysis method, as well as a forecasting method.The purpose of the article is to confirm or refute the hypotheses about the further strengthening of the contradictions between the emergence and implementation of new technologies for processing personal data versus ensuring the protection of human rights, as well as the expediency and possibility of using foreign legislative experience in domestic practice to counter these threats and reduce the risks arising from this and damage.Main results, scope. The article examines the legislative experience of legal regulation of the types, scope, and nature of personal data in the People's Republic of China, the United States of America, the Republic of Belarus, and the Russian Federation. At the same time, Chinese legislation most quickly responds to the challenges of the criminal use of biometric technologies, American legal norms are less acceptable for our practice due to the peculiarities of case law, and Belarusian law has only recently entered into force, opening the era of legal regulation in this area. The facts of the use of new technologies (such as deepfake) for the processing of biometric information for criminal purposes and the problems of law enforcement in this area, as well as legal disputes of citizens who have suffered damage from the use of these technologies, are analyzed. It is predicted that it will be impossible to fully ensure the protection of human rights in the context of the emergence of new technologies for processing personal data. The importance of the desire to predict threats to the protection of personal information at the stage of emergence of new technologies for processing personal data in order to neutralize them in a timely manner is indicated.Conclusion. An analysis of the legislation of foreign countries will make it possible to give preference to the Chinese experience, which promptly counteracts the risks of using new technologies for criminal purposes. An analysis of domestic and global law enforcement practice will make it possible to predict the spread of new ways of committing crimes, the misuse of personal data, and vulnerabilities in their storage and protection. At the same time, excessive restrictions on access to data, their processing and their circulation can make it difficult for law enforcement agencies to solve the tasks of ensuring state security and the protection of public order. It requires constant monitoring of threats and risks and timely technical and legal response to their manifestation. The purpose of the study has been achieved, ways to improve legislation in order to protect human rights in the context of the introduction of digital innovations in all spheres of human activity are proposed. Security, combating crime.